PEPTIDES: A NEW THERAPEUTIC APPROACH - Preet, Payal (International Journal of Current Pharmaceutical Research, 2018)
Peptide therapeutics have played a notable role in medical practice since the advent of insulin therapy in the 1920s. Over 60 peptide drugs are approved in the United States and other major markets, and peptides continue to enter clinical development at a steady pace. Peptide drug discovery has diversified beyond its traditional focus on endogenous human peptides to include a broader range of structures identified from other natural sources or through medicinal chemistry efforts. Peptides are recognized for being highly selective and efficacious and, at the same time, relatively safe and well tolerated. Consequently, there is an increased interest in peptides in pharmaceutical research and development (R and D), and approximately 140 peptide therapeutics are currently being evaluated in clinical trials. Given that the low-hanging fruits in the form of obvious peptide targets have already been picked, it has now become necessary to explore new routes beyond traditional peptide design. Examples of such approaches are multifunctional and cell-penetrating peptides, as well as peptide drug conjugates. In regards to patient compliance for drug delivery, oral drug delivery is generally the preferred route of administration. However, parental injection of peptide drugs has always been the primary method of peptide drug administration. Nevertheless, oral delivery of peptide drug presents a significant challenge due to the enzymatic degradation by enzymes in the GI tract and the poor penetration of the peptides across gastro-intestinal epithelium membranes, particularly for adults. Therefore, a novel peptide drug analogue or pro-drug that both protect peptide drugs from degradation by the enzymes in the GI tract that also improves its penetration across the intestinal epithelium membrane would greatly advance the development of peptide drugs as effective candidates for the treatment of various diseases.